Experimental phase equilibrium data of the system Cu–O–CaO–Al2O3 at copper saturation. (December 2016) - Hamuyuni, Joseph; Klemettinen, Lassi; Taskinen, Pekka
Abstract: Phase equilibria of the system Cu–O–CaO–Al2 O3 at copper saturation was experimentally investigated for the first time using equilibration techniques. Composition of quenched microcrystalline phases were quantified using Electron Probe Micro-Analyzer (EPMA). Liquidus and solubility data at 1150, 1250, and 1300 °C have been obtained based on four-phase equilibria experimental data. There are large differences between calculated values using MTOX database, version 8.1 in MTDATA and experimental results of this study. Graphical abstract: Highlights: Phase equilibria of the system Cu–O–CaO–Al2 O3 in copper saturation experimentally obtained using equilibration techniques. Direct measurements on the liquidus of the system. Solubility of copper in solid phases observed.